МИНЕРАЛОГИЯ ЗОНЫ ГИПЕРГЕНЕЗА ОНДУМСКОГО ЗОЛОТОРУДНОГО УЗЛА (ТУВА) - Ойдуп Ч.К.; Лебедев В.И.; Монгуш А.А.; Изендеева Л.И.; Лебедева М.Ф. (My University, 2005)
The studied paleo-system of the marginal sea island are includes a wide range of ore deposits of ferrous, non-ferrous, and precious metals. Their occurrence conditions and peculiarities of composition depend, first of all, on distribution of the main structure-forming elements and geochemical specialization of ore-magmatic systems. In general, geological setting and metallogenical specialization of ore-forming and magmatic processes in the Ondumskaya island are system make no exclusion and are determined by geochemical peculiarities of volca-nites and granitoids dominating at the area; namely, the Vendian - Early Cambrian contrast type volcanites and the Late Cambrian - Early Ordovician granitoids with variable composition (the Tannu-Ola complex). Complex composition of the ore mineralization is one of the most common features of ore occurrences and deposits revealed within the system, as well as in other geodynamic settings the ore mineralization is represented by nearly mo-nomineral deposits or/and ore fields with specialized individual composition. The studied deposits occur on different hypsometric levels, and each one of them might be attributed to different formational types. However, by the detailed comparison of mineral composition, there were revealed clear features of their similarity, which permit to assign all these deposits to the single type - the gold-bearing polymetallic massive sulfide ore one; with suggestion that these deposits represent different levels of erosion of a single largevolume system. As an evidence, the paper discusses the mineral varieties developed in zone of hypergenesis by example of Dorgun and Te-rektig ore occurrences. There is presented the whole scope of green-colored minerals divided into three groups according to microchemistry data: copper-, phosphorius- and arsenic-bearing. They were more thoroughly distinguished by X-ray and X-ray-spectral analyses.
Keywords: 553.4.03.05; Палеозой::Ордовикская; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская::Вендский